Determination of public service agency financial management budget absorption with religiosity as moderation - Bambang Lesmono; Saparuddin Saparuddin; Nurlaila Nurlaila (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The low rate of the budget absorption in Indonesia occurs frequently, both at the Ministry/Institution (K/L) and Regional Levels. This study aims to analyze what factors cause delays in budget absorption. This research used descriptive quantitative method, the number of respondents was 141 people. Data were collected through field surveys using the nonprobability sampling method. Data were collected in a cross section using a questionnaire, analyzed using SEM-PLS and processed using the SmartPLS 3.2 application. The results showed that HR did not affect budget absorption. Organizational Culture, Regulation and Religiosity affect budget absorption as well Religiosity did not moderate the relationship between HR, Organizational Culture, Regulation and budget absorption. The results of this study indicated that abilities, experience, skills, knowledge, education and training dominate in improving the quality of human resources but have not been able to maximize budget absorption because existing human resources are still lacking, so there is potential for multiple jobs. The guidelines for implementing programs and budgets are not hindered by the policies/rules that are created, and if someone is honest, they will win trust in a variety of areas, including budget management